Teoretyczne podstawy programu metodyki literatury jako przedmiotu nauczania w szkole wyższej = Theoretical principles in the program of literary methodics as a teaching subject in Colleges - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article treats of the necessity of elaborating a generally outlined but sensibly constructed program for teaching literary methodics as a subject in Colleges for future teachers. The main idea concentrates on four principal problems:
Keywords: literatura; nauczanie; szkolnictwo wyższe